GAMBARAN KARAKTERISTIK ANAK PENDERITA TB PARU PADA ANAK USIA 0 – 17 TAHUN DI RUMAH SAKIT UMUM HAJI MEDAN - DITA ANNISA DIARA NASUTION; EKA AIRLANGGA; DELYUZAR .; NURCAHAYA SINAGA (JURNAL ILMIAH MAKSITEK, 2021)
Tuberculosis (TB) is a potentially fatal contagious disease caused Mycobacterium tuberculosis, that can affect almost anypart of the body but is mainly an infection of the lungs. If left untreated or treated inadequately, the outcome is dangerouscomplication and death. According to WHO (World Health Organization) in 2013, incidence of pulmonary TB in the world isestimated that there were 9 million cases. The purpose of this study was to discover description of characteristic patient withpulmonary TB age of 0-17 years at Haji General Hospital Medan. This is a descriptive study with collecting medical record tofind out TB characteristic in children at Haji General Hospital Medan. The subjects of this study are all children who affectedpulmonary TB in accordance with the inclusion criteria. This study use total sampling method. Total of children withpulmonary TB is 128 people, those who were more affected pulmonary TB is boys, 66 children (51.6%), the age mostaffected pulmonary TB is age 1 - 5 years, namely 49 children (38.3%). Based on immunization status, the most affectedpulmonary TB is those which not given BCG immunization, 119 children (93.0%), based on history of contact with adult TBpatient was found that more children did not have a history contact with other patients, 106 children (82.8%), based oncharacteristic of symptoms by scoring pulmonary TB in children is fever, 128 children (100%), and for cough is 122 children(95.3%), then based on nutritional status malnutrition is most widely found, 105 (82%). The most affected pulmonary TB ischildren with male sex, with age of 0 - 5 years, and BCG negative immunization status. Based on characteristic of symptomsby scoring pulmonary TB the most common is fever and chronic cough, with poor nutritional status.